Influence of Rewards System to Career Planning and Success of Employee - Ahmad Mokhtar, Zainal Shahrir (2012)
This quantitative research aims to determine the relationship between rewards system and career planning and career success of an individual. The study is to help to reveal whether rewards system do have any influences of an individual career planning and career success. It will help to identify the most significant rewards that influenced the individual career planning and career success. With this information it would help an organization to relook at their rewards system and decision can be made to either to enhance the most significant rewards or to eliminate it that is not giving any impact. In this study there are two dimensions are measured for Rewards system and they are monetary rewards and non-monetary rewards. Under the two dimensions there are four sub dimensions and they are basic salary, incentives & allowance, recognition and exposure. While the Career Planning and Success has also two dimensions with three sub dimensions. The sub dimensions that measured Career Planning and Success are awareness of self and environment, goal setting and career success. Data was gathered through questionnaires survey that was distributed out to a1 employee, who either employed with private sector or government in Klang Valley. This is to measure and identify whether rewards systems has any influence towards the individual career planning and success. There were five (5) hypotheses tested and the result based on the respond received is three (3) hypotheses is substantiated and the remaining two (2) hypothesis are not. Based on the study that shows, there is a correlation between rewards system and career planning and success. It further indicated that the element in the rewards system have a positive correlation towards the individual career planning and success particularly the non-monetary rewards (Recognition and Exposure). The difference of opinion between the respondent of a private sectors and government shows private sector employees do feel that rewards system have a significant positive influence towards the individual career planning and success while the government sector does not regard it not significant important of the rewards system towards the individual career planning and success. However in terms of gender and age there is no difference in opinion and they are equal respond in opinion with regards to the rewards system towards the individual career planning and success. Implication of the findings, suggestion for future studies and recommendations are suggested